Mentoring in-service chemistry teachers: acquirements as mentees. Issue 2 (4th March 2018) - Saglam Arslan, Aysegul; Unal, Suat; Karataş, Faik Özgür; Cengiz, Canan
Abstract: The aim of this study is to identify a group of chemistry teachers' (mentees) acquirements of mentoring program by analyzing their reflective journals. Four mentees participated in this study and they met with their mentors once a week for eight consecutive weeks. The mentees devised lesson plans as well as activities during the mentoring sessions. After each mentoring session, the mentees were asked to reflect the process and their gains to their journals. The journals were analyzed in two stages; content analysis of the journals and the analysis of the mentees level of reflections. The analysis of the mentees' journals showed that the mentorship program supported the mentees to improve their pedagogical content knowledge; allow them to utilize various methods, techniques, and materials in their lessons. Besides, the mentees indicated that they performed chemistry courses more effectively with the help of the acquirements from the mentoring sessions. The result of this study showed also that mentors can play key roles in supporting professional developments of teachers. It is suggested that rehearsing lesson plans before going into the classroom would make the mentoring sessions more beneficial.